Sequence stratigraphic significance of tidal channel systems in a shallow lagoon (Venice, Italy). (June 2014) - Zecchin, Massimo; Tosi, Luigi; Caffau, Mauro; Baradello, Luca; Donnici, Sandra
The Holocene succession located in the central part of the Venice Lagoon has been investigated by means of high-resolution seismic and core data, which document a full back-barrier depositional environment developed during the last 6 kyr. The studied succession, 4.5–23 m thick, consists of three seismic units bounded at the base by stratal surfaces marked by deep tidal channel incisions, recording main changes in the lagoon hydrodynamics as well as reorganizations of the tidal channel network. The recognized depositional and erosional phases in the lagoon deposits can be linked to both large-scale factors related to the Holocene sea-level rise and local factors in part due to the human impact. In particular, the lower unit is interpreted as the transgressive systems tracts of the Holocene sequence, initially characterized by the accumulation within small estuarine channels incised during the previous phase of subaerial exposure, whereas the upper units are interpreted as the highstand systems tracts, typified by the persistence of the lagoonal environment. The higher stratal surface records a hydrodynamic change related to a local transgression affecting a deltaic area placed just to the south, probably at least in part aided by human interventions. The Holocene succession accumulated in the central part of the Venice Lagoon testifies that the development of stratal surfaces in back-barrier settings, persisting during both transgressive and highstand conditions, may exhibit differences with respect to that predicted by current sequence stratigraphic models, and therefore, it is useful to improve the knowledge of these systems.